Insights of Using Mobile Application to Assess Creative and Creative Thinking of Indonesian Students - Ridhoni, Wahyu; Prigel Kaloka, Tesdiq; Setyosari, Punaji; Kuswandi, Dedi; Ulfa, Saida (EduLine: Journal of Education and Learning Innovation, 2025)
World education organizations such as UNESCO and OECD have determined that creative and critical thinking are core 21st-century skills essential for students to master. Indonesia also views these two skills as very important, thus formulating creative and critical thinking into two of the six dimensions of the Pancasila Learner Profile. This study analyzes the data we collected during a creative and critical thinking assessment experiment with university students using the CC Thinker android application. The investigation was conducted on 46 participants with three assessment sessions. The research results showed that Creative Thinking in men showed a higher value than women. The Critical Thinking of men is more consistent than women. Creative Thinking of undergraduate students is more consistent than D3 students. However, the Critical Thinking of undergraduate students has increased. Creative Thinking of exact students is higher than non-exact students. In Critical Thinking, exact students develop as continuous exams are carried out. Creative thinking of students outside Java or Java is equal but in critical thinking Javanese students are better than students outside Java.